Actas De Las XXXIX Jornadas De Automática, Badajoz, 5-7 De Septiembre De 2018 2020
DOI: 10.17979/spudc.9788497497565.0737
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle pressure analysis of several hydrogel on extrusion-based bioprinting using computational fluid dynamics

Abstract: A c t a sd el a sX X X I XJ o r n a d a sd eA u t om á t i c a ,B a d a j o z ,5-7d eS e p t i em b r ed e2 0 1 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, some CFD models have been developed to understand cell dynamics in a bioprinting process. For example, Gomez-Blanco et al used a 2D triangular mesh method to simulate the effect of inlet velocity on pressures experienced by cells at nozzle tip 17 and the effect of bioink temperature on velocity in bioprinting. 18 Nair et al developed an analytical formulation, which indicated that dispensing pressure makes a greater influence on viability than nozzle diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some CFD models have been developed to understand cell dynamics in a bioprinting process. For example, Gomez-Blanco et al used a 2D triangular mesh method to simulate the effect of inlet velocity on pressures experienced by cells at nozzle tip 17 and the effect of bioink temperature on velocity in bioprinting. 18 Nair et al developed an analytical formulation, which indicated that dispensing pressure makes a greater influence on viability than nozzle diameter.…”
Section: Introductionmentioning
confidence: 99%